Study on financial performance of irinjalakuda town co-operative bank (ITCB) LTD NO.55 - Betssy Baby Edattukaran (College of co-operation, Banking and management, 2009)
The study entitled “Financial Performance of Irinjalakuda Town Co – operative Bank (ITCB) Ltd.No. 55” was undertaken to examine the financial strength and weakness of Irinjalakuda Town Co – operative Bank. For the purpose of the study secondary data were collected from annual reports of the bank. The data were collected for a period of 15 yers i.e. from 1993 – 94 to 2007 08. The financial performance was studied from detailed observation of financial ratios. From the above discussion and analysis the study revealed that the bank was able to attract more deposits every year but this should match with equally efficient deployment of funds. The bank should take care to fix the target for deployment of funds in proportion to the deposit mobilization targets. Otherwise it will affect the interest earning capacity of the bank and hence the profits. By reducing the cost of production and other direct expenses the bank can achieve the gross profit. The bank can start any other trading activities for improving its profitable position.